Estimation of Salivary Resistin, malondialdehyde and Lipid Profile levels in patients with Diabetes Mellitus - Entedhar R. Sarhat; Rajaa S. Najim; Emad H. Abdulla (Tikrit Journal of Pure Science)
The present study is designed to verify the changes of resistin, malondialdehyde (MDA), glucose and lipid profile in type2 diabetes mellitus.